1999
DOI: 10.1007/s002800050855
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics, tissue distribution, and therapeutic effectiveness of cisplatin encapsulated in long-circulating, pegylated liposomes (SPI-077) in tumor-bearing mice

Abstract: Based on the results of our studies, encapsulation of cisplatin in long-circulating pegylated liposomes has overcome limitations experienced with other liposomal cisplatin formulations. SPI-077 has a prolonged circulation time and increased tumor Pt disposition, and its antitumor effect is significantly improved compared to cisplatin in murine colon and lung cancer models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
149
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 10 publications
12
149
1
1
Order By: Relevance
“…2 Moreover, the increased circulation time allows enhanced liposome accumulation in the areas with compromised vasculature, such as sites of inflammation and tumors. [3][4][5][6][7] A number of preclinical studies reported that drug encapsulation in liposomes increases the efficacy of several anticancer agents both in vitro and in vivo. In particular, liposome formulations of doxorubicin and daunorubicin exhibit a higher antitumor activity and reduced toxicity compared to the free form of the drugs in several experimental tumors and are able to overcome drug resistance.…”
mentioning
confidence: 99%
“…2 Moreover, the increased circulation time allows enhanced liposome accumulation in the areas with compromised vasculature, such as sites of inflammation and tumors. [3][4][5][6][7] A number of preclinical studies reported that drug encapsulation in liposomes increases the efficacy of several anticancer agents both in vitro and in vivo. In particular, liposome formulations of doxorubicin and daunorubicin exhibit a higher antitumor activity and reduced toxicity compared to the free form of the drugs in several experimental tumors and are able to overcome drug resistance.…”
mentioning
confidence: 99%
“…Data from tumour-bearing mouse models showed a significantly greater antitumour activity compared to cisplatin and a significantly increased tumour exposure to platinum. This coincided with a decreased platinum exposure to the kidneys, the principal organ of cisplatin toxicity (Newman et al, 1999). On the basis of these preclinical results, in addition to the previous success of STEALTH ® liposomal doxorubicin, phase I studies in both adult and paediatric patients, with advanced cancer not amenable to other cancer treatments, were performed in the UK and Europe.…”
Section: Discussionmentioning
confidence: 92%
“…The pharmacokinetics of SPI-77 were significantly altered from those associated with cisplatin treatment and implied that the cisplatin was maintained inside the liposome with no detectable free cisplatin measured in plasma at any point following administration. Although preclinical data suggested that low plasma levels of free cisplatin would explain the lack of toxicity seen with SPI-77 in murine tumour models, the complete retention of cisplatin within the liposomes was not predicted as significant antitumour activity was observed (Newman et al, 1999). Both the paediatric and adult phase I studies were stopped at a dose of 320 mg m -2 in order to address the issue of reformulation of liposomally bound cisplatin, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This action results in increasement of drug accumulation in tumor due to an increase in entrapment and permeability of blood vessels. For more selective delivery of cisplatinum to tumors, this drug is used as conjugation of drug-dissolved polymer, colloid nanocarriers like pegylated liposomes, poly aspartic acidpoly ethylene glycol micelles, poly caprolactone-poly ethylene glycol micelles, poly caprolactone-poly 2-(N,Ndimethylamino) ethyl methacrylate micelles [3][4][5][6][7][8][9]. No carrier able to deliver cisplatinum to tumors effectively is developed yet.…”
Section: Introductionmentioning
confidence: 99%